2016
DOI: 10.1007/s10459-016-9686-5
|View full text |Cite
|
Sign up to set email alerts
|

An autoethnographic exploration of the use of goal oriented feedback to enhance brief clinical teaching encounters

Abstract: Supervision in the outpatient context is increasingly in the form of single day interactions between students and preceptors. This creates difficulties for effective feedback, which often depends on a strong relationship of trust between preceptor and student. Building on feedback theories focusing on the relational and dialogic aspects of feedback, this study explored the use of goal-oriented feedback in brief encounters with learners. This study used autoethnography to explore one preceptor's feedback intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 24 publications
2
32
0
Order By: Relevance
“…The focus on goals and iterative loops within and across encounters offers structure but is not prescriptive. Through establishing shared goals and activities, an educational alliance is strengthened and can then be leveraged for behaviour change . The three components interplay in the sense that if an educator takes the time to discuss and negotiate goals and an agreement about how to work towards the goals, this demonstrates that the supervisor is invested in the learner and thereby strengthens perceptions of trust and respect (ie the bond).…”
Section: Myth 2: Feedback Is a Teacher Skillmentioning
confidence: 99%
See 2 more Smart Citations
“…The focus on goals and iterative loops within and across encounters offers structure but is not prescriptive. Through establishing shared goals and activities, an educational alliance is strengthened and can then be leveraged for behaviour change . The three components interplay in the sense that if an educator takes the time to discuss and negotiate goals and an agreement about how to work towards the goals, this demonstrates that the supervisor is invested in the learner and thereby strengthens perceptions of trust and respect (ie the bond).…”
Section: Myth 2: Feedback Is a Teacher Skillmentioning
confidence: 99%
“…Shared educational principles across these two approaches include acknowledgement of the importance of establishing (and re‐establishing) relationships, discussion and setting of goals, the active engagement of the learner, iterative feedback loops and a focus on learner development. Neither is prescriptive in flavour, but they offer structure, which is appreciated by educators . When feedback conversations are oriented towards improvement, the ritualised hang‐ups around positive and negative content and the myriad of behaviours (such as avoidance or sugar‐coating) described above are broken.…”
Section: Myth 2: Feedback Is a Teacher Skillmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the others in my journey included other participants in my culture, my research team and relevant literature. 5 'Travel companions' help to provide different angles and perspectives on a study and deepen what is discovered along the way. They allow the focus of research to be on what is experienced or lived by the self and others in that culture, not on the researcher alone.…”
mentioning
confidence: 99%
“…I found that during my journey, the self-reflective process strengthened my understanding of the culture in which I worked, resulting in the evolution and strengthening of my personal practice. 5 Furthermore, the sharing of narratives and their analysis and interpretation of the interconnectivity of self and others in a particular culture ideally will resonate with readers. They may then be motivated to reflect on how the findings fit within their own teaching or learning environments.…”
mentioning
confidence: 99%